Effects of Extraction Temperature and Particle Size on Quality of Edible Oil from Podocarpus Falcatus Seed by Aqueous Method, Ethiopia - Daniel Alemu Goben; Solomon Abera; Anbesse Girma Shewa; Sisay Feleke (Journal of Food Science and Nutrition Therapy - Peertechz Publications, 2022)
Objective: The kernel from Podocarpus falcatus has potential for the production of edible oil. The oil is currently extracted using a traditional inefficient method for the purpose of household consumption. The objective of this study was to investigate the effects of particle size and extraction temperature on the yield and quality of oil extracted from P. Falactus seeds by the aqueous method. The experiment was carried out in a completely randomized design that comprised of three aqueous temperatures (70, 80, and 900C) and three particle sizes (0.25, 0.50, and 0.75mm).  Results: The maximum oil yield in this study was obtained at 22.29 and 22.38±2.10% at an extraction temperature of 70°C and the particle size of 0.5mm respectively. Particle size and oil yield have a correlation in that higher extraction were obtained (25%) as the particle size decreased. The particle size and temperature interaction had a positive effect on yield and maximum oil yield (25.25%) was obtained by the combination of 0.25mm particle size and 70°C. The peroxide, iodine, and saponification values were obtained with an acceptable range by the combination of 0.25mm and within the acceptable limit of edible oil 70°C. Yield and oil quality were influenced by extraction particle size and temperature.